2018
DOI: 10.1155/2018/9045820
|View full text |Cite
|
Sign up to set email alerts
|

Application of Linear Viscoelastic Properties in Semianalytical Finite Element Method with Recursive Time Integration to Analyze Asphalt Pavement Structure

Abstract: Traditionally, asphalt pavements are considered as linear elastic materials in finite element (FE) method to save computational time for engineering design. However, asphalt mixture exhibits linear viscoelasticity at small strain and low temperature. erefore, the results derived from the elastic analysis will inevitably lead to discrepancies from reality. Currently, several FE programs have already adopted viscoelasticity, but the high hardware demands and long execution times render them suitable primarily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Long-term behavior is both affected by creep and drying shrinkage at the same time. erefore, r t , the rate of creep and drying shrinkage over time, were derived from the average of (13) and (14) as shown in (15). Figure 1 shows the graphs of creep and drying shrinkage rates over time.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term behavior is both affected by creep and drying shrinkage at the same time. erefore, r t , the rate of creep and drying shrinkage over time, were derived from the average of (13) and (14) as shown in (15). Figure 1 shows the graphs of creep and drying shrinkage rates over time.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…However, the reliability of such predictions has not been sufficiently verified, and these methods are difficult and complicated for designers to understand and use. In addition, due to recent advances in computer technology, many researchers are trying to predict and evaluate the long-term behavior of PSC bridges by numerical analysis using the finite difference method or finite element method [12][13][14][15][16][17], but for designers, a simple and clear prediction method is more preferable.…”
Section: Introductionmentioning
confidence: 99%
“…In finite element modeling on a global scale, pavement is usually deemed a homogenous material in order to reduce computational costs. Previous studies demonstrated that simplification would not significantly affect simulation accuracy only if it was employed under proper mesh treatment [2,3]. On a local scale, two approaches are feasible for constructing an asphalt mixture model, depending on the simulation's purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Stress state analysis and structural dynamic response calculation in asphalt pavement are essential for the design, construction, and maintenance [33]. Choosing a constitutive model that can adequately characterize the material and precisely estimate its characteristics is essential to obtaining a real and accurate stress state and structural dynamic response [34].…”
Section: Introductionmentioning
confidence: 99%